THE NOTION OF CONCEPTUAL INFORMATION, ITS LOGICAL AND LINGUISTIC FOUNDATIONS - Bektoshev Otabek Kodiraliyevich; Ergasheva Zarnigor Hasanjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with the notion of conceptual information in linguistics. As soon as a person is born, he becomes a participant and observer of events happening in the environment. It understands the realities of the world, analyzes and compares various objects and processes. As a result, a person absorbs a certain experience, knowledge, assimilates it into his mind, and a conceptual image of the world is formed in his mind, consisting of concepts of different levels of complexity and abstraction.